Multidrug Efflux Pumps at the Crossroad between Antibiotic Resistance and Bacterial Virulence - Alcalde-Rico, Manuel; Hernando-Amado, Sara; Blanco, Paula; Martínez, José L. (Frontiers in Microbiology, 2016)
Multidrug efflux pumps can be involved in bacterial resistance to antibiotics at different levels. Some efflux pumps are constitutively expressed at low levels and contribute to intrinsic resistance. In addition, their overexpression may allow higher levels of resistance. This overexpression can be transient, in the presence of an effector (phenotypic resistance), or constitutive when mutants in the regulatory elements of the expression of efflux pumps are selected (acquired resistance). Efflux pumps are present in all cells, from human to bacteria and are highly conserved, which indicates that they are ancient elements in the evolution of different organisms. Consequently, it has been suggested that, besides antibiotic resistance, bacterial multidrug efflux pumps would likely contribute to other relevant process of the microbial physiology. In the current article, we discuss some specific examples of the role that efflux pumps may have in the bacterial virulence of animals' and plants' pathogens, including the processes of intercellular communication. Based in these evidences, we propose that efflux pumps are at the crossroad between resistance and virulence of bacterial pathogens. Consequently, the comprehensive study of multidrug efflux pumps requires addressing these functions, which are of relevance for the bacterial-host interactions during infection.